Synthesis and Characterization of Mixed Ligand Complexes of Thorium(IV) with Piperidinobenzylurea and Various Anions - Viswanathan, M.; Krishnan, G. (Asian Journal of Chemistry, 2016)
A series of four mixed ligand complexes of Th(IV) with piperidinobenzylurea (PBU) and various anions such as acetate, nitrate, perchlorate and thiocyanate have been synthesizd and characterized. The chemical composition of the complexes have been established from analytical, molar conductance, spectral and thermal studies. Antimicrobial activity of the complexes was also studied. The complexes exhibit the formulae: [Th(PBU)2X4] where X = NO3, NCS– or CH3COO– and [Th(PBU)3ClO4](ClO4)3. In these complexes, the ligand, PBU acts as a neutral bidentate ligand whereas the monovalent anions act as unidentate ligands.